Utilization of Website-Based Information Systems to Optimize Data Management in Khaela Hijab: Pemanfaatan Sistem Informasi Berbasis Website Sebagai Optimalisasi Pengelolaan Data Pada Khaela Hijab - Sharazita Dyah Anggita (Universitas Lancang Kuning, 2023)
Khaela Hijab is a company which sells hijab products. The place is in Sedayu District, Bantul Regency, Yogyakarta. Khaela Hijab produces their own hijab and markets its products via offline and online. Khaela Hijab uses social media as a medium to promote the products. Every sales and purchase transactions are recorded conventionally in a special note book. The transaction writing model causes constraints in presentation of information, where the information could not provided in real time. Beside of that, the calculation of sales profit product also had constraint which caused by recording of production and sales costs that often unbalanced. The result of this activity is the usage of sales information system which uses website as a base - with assistance and material distribution about the use of website to optimize the data management.